PLENTY, a hydroxyproline O-arabinosyltransferase, negatively regulates root nodule symbiosis in Lotus japonicus. (23rd October 2018) - Yoro, Emiko; Nishida, Hanna; Ogawa-Ohnishi, Mari; Yoshida, Chie; Suzaki, Takuya; Matsubayashi, Yoshikatsu; Kawaguchi, Masayoshi
Abstract : The gene responsible for the plenty hypernodulation phenotype in Lotus japonicus was identified. The enzymatic activity and Golgi localization of PLENTY demonstrated its function as a post-translational modification enzyme. Abstract: Legumes can survive in nitrogen-deficient environments by forming root-nodule symbioses with rhizobial bacteria; however, forming nodules consumes energy, and nodule numbers must thus be strictly controlled. Previous studies identified major negative regulators of nodulation in Lotus japonicus, including the small peptides CLAVATA3/ESR (CLE)-RELATED-ROOT SIGNAL1 (CLE-RS1), CLE-RS2, and CLE-RS3, and their putative major receptor HYPERNODULATION AND ABERRANT ROOT FORMATION1 (HAR1). CLE-RS2 is known to be expressed in rhizobia-inoculated roots, and is predicted to be post-translationally arabinosylated, a modification essential for its activity. Moreover, all three CLE-RSs suppress nodulation in a HAR1-dependent manner. Here, we identified PLENTY as a gene responsible for the previously isolated hypernodulation mutant plenty . PLENTY encoded a hydroxyproline O -arabinosyltransferase orthologous to ROOT DETERMINED NODULATION1 in Medicago truncatula . PLENTY was localized to the Golgi, and an in vitro analysis of the recombinant protein demonstrated its arabinosylation activity, indicating that CLE-RS1/2/3 may be substrates for PLENTY. The constitutive expression experiments showed that CLE-RS3 was the major candidate substrate for PLENTY, suggesting the substrate preference of PLENTY for individual CLE-RS peptides. Furthermore, a genetic analysis of the plenty har1 double mutant indicated the existence of another PLENTY-dependent and HAR1-independent pathway negatively regulating nodulation.